2020
DOI: 10.1016/j.clay.2020.105757
|View full text |Cite
|
Sign up to set email alerts
|

ZnTi layered double hydroxides as photocatalysts for salicylic acid degradation under visible light irradiation

Abstract: A series of ZnTi layered double hydroxides (LDH) with different Zn/Ti ratios are prepared and used as catalysts for photodegradation of salicylic acid (SA) under visible light. The catalysts are characterized by X-Ray diffraction, diffuse reflectance infrared Fourier transform spectroscopy, UV-vis diffuse reflectance spectroscopy, thermogravimetry, electron paramagnetic resonance and N2 adsorption-desorption. The results show that SA anions bind to the LDH surface and that an electron can be excited from the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The ZnTi-LDH sample at all temperatures displays a strong absorption band due to the ligand-to-metal charge transfer involving the octahedrally coordinated Zn and Ti atoms within the layered network. 36 With the increase of irradiation temperature from 30 °C to 250 °C, the absorption intensity of visible light and ultraviolet light for ZnTi-LDH is sharply enhanced and an obvious red-shift of the absorption band is observed. According to Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The ZnTi-LDH sample at all temperatures displays a strong absorption band due to the ligand-to-metal charge transfer involving the octahedrally coordinated Zn and Ti atoms within the layered network. 36 With the increase of irradiation temperature from 30 °C to 250 °C, the absorption intensity of visible light and ultraviolet light for ZnTi-LDH is sharply enhanced and an obvious red-shift of the absorption band is observed. According to Fig.…”
Section: Resultsmentioning
confidence: 98%
“…A ZnTi−LDH prepared with urea in the homogeneous co-precipitation method showed the superior removal of colorless salicylic acid (SA) under visible light irradiation, which was much higher than that of commercial P25. The Zn 2+ and Ti 4+ cations were highly dispersed on the brucite-like LDH sheets, effectively promoting charge separation and leading to excellent photocatalytic activity [65]. In addition, a ZnTi−LDH with a laminated architecture was deemed an effective and stable visible-light-induced photocatalyst [38,66].…”
Section: Pure-phase Ldhsmentioning
confidence: 99%
“…The results suggested that MCr NO 3 -LDHs (M = Cu, Ni) exhibit 20 times higher photocatalytic activity than P25 as well as excellent recycling ability. 8 Thus, the powerful photocatalytic performance made investigators realize the broad application prospects of LDHs in photocatalysis, such as dyes (rhodamine B, rhodamine 6G), 9 methylene blue degradation, 10,11 NO x gases (NO and NO 2 ) removal, 12 salicylic acid degradation, 13 CO 2 conversion, 14 and pesticide degradation. 15 However, there are few studies on the photocatalytic degradation of PPCPs by LDHs, including but not limited to NPX.…”
Section: Introductionmentioning
confidence: 99%